The opinions of the first episode teachers on the training courses based on active learning methods "A field study in basic education schools, the first episode in Latakia" - أحمد مطيعة; كنجو راما (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The aim of the current research is to identify the opinions of teachers of the first cycle of basic education about training courses based on methods of active learning, and to identify the differences in the opinions of teachers according to gender variables and years of experience. The sample of the research reached (316) teachers who were randomly chosen from schools in Lattakia city, As the number of members of the original community according to the statistics of the Directorate of Education for the year 2019-2020 (2632) male and female teachers. To reach the objectives of the research, a questionnaire was designed on the training courses based on the active learning methods prepared by the researcher (Appendix 1). The results showed that the opinions of teachers were high about the importance of the training sessions, and the results also showed that there were no differences due to the gender variable, and that there were differences between teachers ’opinions of the variable of years of experience in favor of those with more than 5 years of experience.